Fixed-Life or Rechargeable Batteries for Deep Brain Stimulation: Preference and Satisfaction Among Patients With Hyperkinetic Movement Disorders - Qiu, Xian; Wang, Yuhan; Lin, Zhengyu; Wu, Yunhao; Xu, Wenying; Wu, Yiwen; Sun, Bomin; Ashkan, Keyoumars; Zhang, Chencheng; Li, Dianyou (Frontiers in Neurology, 2021)
Background: Deep brain stimulation (DBS) is an established treatment for hyperkinetic movement disorders. Patients undergoing DBS can choose between the use of a rechargeable or non-rechargeable battery for implanted pulse generators (IPG). Objectives: In this study, we aimed to evaluate patient preferences and satisfaction with rechargeable and non-rechargeable batteries for IPGs after undergoing DBS. Methods: Overall, 100 patients with hyperkinetic movement disorders (dystonia: 79, Tourette syndrome: 21) who had undergone DBS took a self-designed questionnaire to assess their satisfaction and experience with the type of battery they had chosen and the factors influencing their choice. Results: Of the participants, 87% were satisfied with the stimulating effects of the treatment as well as the implanted device; 76% had chosen rechargeable devices (r-IPGs), 71.4% of whom recharged the battery themselves. Economic factors were the main reason for choosing both r-IPG and non-rechargeable IPG (nr-IPG). The questionnaire revealed that 66% of the patients checked their r-IPG battery every week. The mean interval for battery recharge was 4.3 days. Conclusions: The majority of the patients were satisfied with their in-service-IPG, regardless of whether it was a r-IPG or nr-IPG. Affordability was the main factor influencing the choice of IPG. The majority of the patients were confident in recharging the battery of their r-IPG themselves; only 11% of patients experienced difficulties. Understanding the recharge process remains difficult for some patients and increasing the number of training sessions for the device may be helpful.